To Assess the Knowledge of Mothers in Relation to Selected Aspect of Immunization - Kishor Joshi, Harshada; Sawant, Suchita; Rasaria, Shweta (Innovational: Journal of Nursing and Healthcare, 2024)
Background: Immunization is the most cost-effective public health intervention to protect the child from diseases. It is profoundly tragic that almost 2 million children still die each year from diseases for which vaccines are available. Objectives: The objective of the study was to assess the knowledge of the mother regarding immunization and to correlate the knowledge of the mothers regarding immunization with selected demographic variables. Methods: A descriptive approach was used for the study. The study was conducted in Chuim Community, Khar Danda. Non-probability convenient sampling technique was adopted for sample selection. They were selected as per criteria laid down for the selection of the sample study and consisted of 50 samples. The data gathering process began from September 10, 2017, to September 20, 2017. The data collected were analyzed in terms of frequency percentage. Results: The majority of sample belong the age group of 23–27 years, i.e., 48% (24) and 28–32 years, i.e., 36% (18). About 38% (19) of mothers were belonging to education primary and 78% (39) of mothers were housewife. About 70% (35) of mothers have the children between the age group of 1 and 5 years. About 22% (11) of mothers had knowledge of pentavalent vaccination, it site, doses and management and disease prevented by vaccine. About 72% (36) of mothers had knowledge of bacillus Calmette–Guérin (BCG) vaccine among the 50 sample. About 50% (25) of mothers had knowledge of measles, mumps, and rubella (MMR) vaccine among the 50 sample. About 84% (42) of mothers had knowledge of side effect of injectable vaccine and its reason behind the side effect. About 48% (24) of mothers had knowledge of the management of side effect of vaccine. Conclusion: This research concluded, it proves that the community was unaware of newer vaccination (pentavalent vaccine) and also in some cases, community was unaware of the management and side effect of vaccines. Majority of samples know about the immunization, i.e., BCG and MMR vaccines, but majority of samples are not having adequate knowledge of the pentavalent vaccine.